Synthesis and Characterization of Chrysanthemic Acid Esters - Ding, Qingwei; Li, Yonghong; Zhang, Mingang (Asian Journal of Chemistry, 2012)
A short and convenient synthesis for a series of novel chrysanthemic acid esters from aldehyde and chrysanthemic acid is reported.